7.7k views
1 vote
Type the correct answer in the box

Type the correct answer in the box-example-1
User GPI
by
6.1k points

1 Answer

2 votes

Answer:


w=V/(lh)

Explanation:

Let

l------> the length of the base of the prism

w------> the width of the base of the prism

h------> the height of the prism

we know that

The volume of the prism is equal to


V=lwh

Solve for w

That means-------> isolate the variable w

so

Divide both sides by (lh)


V/(lh)=lwh/(lh)

Simplify


w=V/(lh)

User Reesjones
by
6.9k points